Pengaruh Fasilitas Dan Kompensasi Terhadap Kinerja Guru SMK Plus Al-Farhan Sukabumi - Dewi Sum; Muhammad Ridwan; Koesmawan Koesmawan (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2024)
This study aims to test and analyze the Effect of Facilities and Compensation on Teacher Performance at SMK Plus Al-Farhan Sukabumi. This type of research is quantitative research. The data used in the study were primary data obtained from questionnaires distributed to teachers at SMK Plus Al-Farhan Sukabumi. The sampling technique used is saturated sampling, meaning that all members of the population are used as samples. The number of samples used was 35 respondents. The data obtained were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests and determination tests using the SPSS Version 25 program (Statistical Package for the Social Sciens). The partial test results with a table of 2.035 for facilities had a significant effect on teacher performance with a calculated value of 2.169 (2.169 > 2.035) and a significance number of 0.038 (0.038 < 0.05). Compensation had a significant effect on teacher performance with a calculated value of 2.465 (2.465 > 2.035) and a significance number of 0.019 (0.019 < 0.05). While simultaneous testing for facilities and compensation had a significant effect on teacher performance with a calculated f value of 10.572 (10.572 > 3.29) and a significance number of 0.000 (0.000 < 0.05). This research is expected to be one of the additional references regarding Work Facilities, Compensation and Teacher Performance.